Dampak Restrukturisasi Perjanjian Kredit Terhadap Jaminan HakTanggunganDalam Upaya Penyelamatan Kredit Bermasalah - suryati; Teguh Anindito; Aris Priyad (Wijayakusuma Law Review, 2024)
The aim of this research is to determine the impact of credit agreement restructuring on mortgage guarantees in aneffort to rescue problem loans. To achieve this goal, the approach method used is empirical juridical. Data sourcesinclude primary data and secondary data. Primary data is data obtained directly by conducting field research in theform of free, guided interviews with respondents. Meanwhile, secondary data consists of primary legal materials,secondary legal materials and tertiary legal materials. The data obtained was then analyzed qualitatively.Conclusion: Based on the results of research and analysis of data collected by the author, it is concluded that theimpact of credit agreement restructuring on mortgage guarantees in efforts to save problematic loans is: theposition of collateral whose credit agreement has been restructured through an addendum deed is that theguarantee remains valid because the object of the guarantee Bank Jateng has charged it with a guarantee institutionin the form of a mortgage which has the characteristic of always following the object being pledged as collateral inthe hands of whoever the object is in (droid de suite). Then, for the initial credit agreement which has beenrestructured through an addendum, it remains in effect as a binding condition between legal subjects in their legalrelationship and the addendum cannot be separated from the original credit agreement.Keywords: Impact, Restructuring, Credit Agreement, Mortgage Rights, Problematic Credit